The impact of cultural capital on development of entrepreneurship in Wales - Balaussa Azubayeva (Administrative Sciences, 2021)
The focus of this paper is the impact of parental cultural capital on offspring's occupational choice in relation to entrepreneurship. Despite growing interest to cultural motives for entrepreneurship on an individual level, few studies link these two domains empirically. This study follows the Culture Based Development research paradigm (CBD) developed by Tubadji and explores how culture influences occupational choices of school graduates during school-to-work transition. The main hypothesis of this paper is that sons of entrepreneurs are more likely to choose transitions into entrepreneurship after graduating school. I test three hypotheses on a unique historic dataset from Wales, UK, employing Probit analysis. I found a significant correlation between entrepreneurial background of father and son's entrepreneurial entry. Poor socio-economic status of a father is also a predictor of entry into entrepreneurship of their son, motivated by necessity. The findings of this research contributed to the applicability of CBD to a historic dataset of earlier periods to capture a significant cultural impact on entrepreneurship development in Wales, UK.
Keywords: 350; entrepreneurship; cultural capital; culture; Culture Based Development